Polybrominated diphenyl ethers in road and farmland soils from an e-waste recycling region in Southern China: Concentrations, source profiles, and potential dispersion and deposition - Luo, Yong; Luo, Xiao-Jun; Lin, Zhen; Chen, She-Jun; Liu, Juan; Mai, Bi-Xian; Yang, Zhong-Yi (The Science of the total environment, 2009)
The present study analyzed road soils collected near the dismantling workshops of an e-waste recycling region in South China to determine the PBDE profiles. Farmland soils at a distance of about 2 km from the dismantling workshops were also collected to evaluate the potential dispersion and deposition of PBDEs in the surrounding environment. Total PBDE concentrations ranged from 191 to 9156 ng/g dry weight in road soils and from 2.9 to 207 ng/g dry weight in farmland soils, respectively. Three PBDE source profiles were observed from the road soils by principal component analysis, and were compared with the congener patterns in different technical products. Elevated abundances of octa- and nona-congeners were found in the “deca-” derived PBDEs as compared with the deca-BDE products. The results in this study suggest that debromination of BDE 209 may have occurred during the use of electric and electronic equipment and/or another technical formulation (Bromkal 79-8DE) was also likely the source of octa- and nona-congeners in e-wastes. Comparison of the PBDE patterns in road and farmland soils implied that the PBDEs in farmland soils have been subject to complex environmental processes.